295 NUCLEOLIN, A NOVEL TARGET FOR APTAMER-BASED ANTICANCER THERAPY. (1st January 2005) - Miller, D. M.; Bates, P.; Trent, J.; Sharma, V.; Thomas, S.; Barnhart, K.; Laber, D.
Abstract : AGRO100, a G-rich oligonucleotide is an extremely stable molecule which is stabilized by G-quartet formation. It has growth inhibitory activity for malignant cells which correlates with binding to a target protein, nucleolin. Nucleolin is a multifunctional protein which plays an important role in regulating ribosomal RNA synthesis and processing as well as DNA replication. We have shown that nucleolin is present on the surface of transformed, but not normal cells. Nucleolin binding results in translocation of the oligonucleotide to the cell nucleus. AGRO100 is growth inhibitory for a wide variety of tumor cell T types, causing S-phase arrest and inducing apoptosis. Its growth inhibitory activity is synergistic with a number of chemotherapeutic agents. A phase I clinical trial was performed to determine the clinical toxicity of AGRO100. Seventeen patients were treated with a four-day infusion of AGRO100. Five patients with evidence of clinical response or stable disease were given an additional monthly course of AGRO100. No clinical or laboratory toxicity was noted. Significant clinical activity was seen in these patients. In summary, the G-rich oligonucleotide AGRO100 inhibits cancer cell growth by binding to nucleolin. There is evidence of clinical activity without significant toxicity.